2023
DOI: 10.1021/acsami.3c07343
|View full text |Cite
|
Sign up to set email alerts
|

Origami-like 3D Fog Water Harvestor with Hybrid Wettability for Efficient Fog Harvesting

Abstract: Collecting water in fog has also become a breakthrough to solve the hidden danger of water shortage in some arid areas. The three-dimensional (3D) structure fog collection material can increase the surface area in direct contact with the fog flow and reduce the quick flow of fog, which can effectively improve the fog collection efficiency. Imitating the three-dimensional structure of corrugated paper, the 3D fog collecting material with hybrid wettability was prepared by chemical and physical means. We discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In the low-curvature state ( R = 70 mm), the collection efficiency of convex samples is much lower than that of concave samples. This is due to the generation of airflow vortices, increasing the droplet falling speed . Meanwhile, the weight of collected water of the concave surface with a diameter of 50 and 60 mm is similar.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…In the low-curvature state ( R = 70 mm), the collection efficiency of convex samples is much lower than that of concave samples. This is due to the generation of airflow vortices, increasing the droplet falling speed . Meanwhile, the weight of collected water of the concave surface with a diameter of 50 and 60 mm is similar.…”
Section: Resultsmentioning
confidence: 89%
“…This is due to the generation of airflow vortices, increasing the droplet falling speed. 55 Meanwhile, the weight of collected water of the concave surface with a diameter of 50 and 60 mm is similar. Furthermore, a SSH-patterned surface with lengths of 60, 70, and 80 mm and a width of 50 mm, respectively, is rolled into cylindrical shape for water collection, as displayed in Figure 7a.…”
Section: ■ Experimental Partmentioning
confidence: 99%
“…Studies have shown that 3D-structured materials exhibited improved fog collection performance, attributable to their large specific surface area. 27,28 In other words, introducing 3D structures compared to two-dimensional (2D) or onedimensional (1D) structures provides a larger area for the fog droplet to be captured. Once the contact area increases, the droplet capture and transportation area increases, leading to more area available for droplet contact with the surface and facilitating droplet harvesting.…”
Section: Introductionmentioning
confidence: 99%